Challenges Faced and Factors Affecting Improvement: First-Year Undergraduate Students’ Perceptions of Academic Writing - Hariyanti, Yuni; Duwi Purwandari, Junita; Rotjanawongchai, Satima (Jurnal Konatif: Jurnal Ilmiah Pendidikan, 2025)
Academic writing is one of the required courses that first-year students must undertake. It can be particularly challenging, considering the students might have never taken such a course in high school. This study sought to understand students’ familiarity with academic writing and determine the factors affecting undergraduate students’ academic writing improvement. This descriptive study used multi methods combining quantitative and qualitative, employing both closed and open-ended questionnaires as the main data source. The participants were 129 first-year undergraduate students majoring in Political Science and taking an academic writing course in semester one. Data analysis showed that while most students were familiar with the types and structures of academic writing, they did not understand how to build strong introductory and body paragraphs. This study also revealed intrinsic and extrinsic factors affecting students’ academic writing improvement. The practical implications of this study were twofold. Firstly, the university needs to examine and improve the academic writing course syllabus so students can taste a better learning experience leading to an improved understanding of academic writing. Secondly, students should start taking more responsibility for their academic writing learning instead of just relying on the lecturers for information.